Viral evolution and Immune responses - Pilar Domingo-Calap (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2019)
Antiviral responses are activated rapidly after viral infection in order to control and prevent dissemination of the virus. Different pathways are activated in the immune system, including innate and adaptive responses. On the other hand, viruses have evolved specifi c strategies to evade these responses. Due to the high viral evolutionary rates, escape variants can emerge and spread fast in the population. The co-evolution between viruses and their host is a constant arms race, and is of special interest to understand the viral escape mechanisms that may guide the future development of antiviral treatments and vaccines.